Two new species of the genus Habrobathynella Schminke, 1973 (Syncarida, Parabathynellidae) from the southwestern peninsular India - Elia, Bandari; Shaik, Shabuddin; Reddy, Yenumula Ranga (Zootaxa, 2016)
The genus Habrobathynella Schminke, 1973, comprises 14 species: two from Madagascar and 12 from the peninsular India. Two more new hyporheic species of this genus, viz. H. muvattupuzha n. sp. and H. adishankara n. sp., from the southwestern peninsular India, are described and illustrated, and their position in the genus is discussed. Both new species are more closely related to each other than to their hitherto known congeners. H. muvattupuzha n. sp. has a unique combination of characters: male Th VIII small in size, with protopod distinctly expanded latero-externally, and basipod balloon-shaped; uropodal sympod with inhomonomous row of five spines, with penultimate spine longer and thicker than others, and ultimate spine same as proximal spines; paragnaths with minaret-like smooth coupler and short lateral lobes; fifth antennular segment with only two long aesthetascs; and first maxillary segment with two setae. H. adishankara n. sp. is distinct from its congeners in having a unique set of characters: uropodal sympod with inhomonomous row of six spines, with penultimate and ultimate spines as in the preceding species; paragnaths with thumb-like, smooth coupler and small lateral lobes; first antennary segment nearly as long as the second one; fifth antennular segment with three long aesthetascs; and first maxillary segment with one seta. The principal morphological characters and their states among the Habrobathynella species, with special reference to the new species, are briefly discussed. Also, brief notes on the ecology and biogeography are given, as is an updated key to Habrobathynella species.